SOUTH CHERPUK AND NORTH CHERPUK - THE LARGEST HOLOCENE MONOGENETIC VOLCANOES ON THE SREDINNYI RANGE OF KAMCHATKA - Pevzner M.M.; Melekestsev I.V.; Volynets O.N.; Melkii V.A. (My University, 2000)
Two volcanic centers, South and North Cherpuk Volcanoes, were investigated on the Sredinnyi Range of Kamchatka. The aim of the work was to study the morphology and structure of cinder cones and lava flows and the compositions of their rocks. The volumes of the erupted materials were calculated for both volcanoes (> 2 km 3 each). A carbon-14 age of ( ∼ 3550 years B. P.) was measured for the first time for the South Cherpuk Volcano and an age of -1740 years A. D. was inferred for North Cherpuk. The genesis of these volcanic centers is discussed.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен